Reliable scheme for the cluster-based communication protocol in wireless sensor networks - ZHOU Zu-de; HU Peng; LI Fang-min (Tongxin xuebao)
Since the data-centric sensing task focuses more on the data reliability,many cluster-based communication protocols were failed to analyze the reliability of the sensing task. The RBD （reliability block diagram） was used to model the data reliability of cluster-based wireless sensor networks （WSN）. The value of reliability was adopted into the cluster formation scheme. Then the malfunctioning node （MN） that could affect the data reliability is defined and analyzed. A detecting scheme was proposed to detect the MN and the friendly node （FN） is used to mitigate its negative effects. Based on the above analysis,the REECP （reliable energy-efficient cluster-based protocol） was proposed. Simulation results demonstrate REECP can prolong the effective lifetime of the network and mitigate the error propagation in data aggrega-tion of sensing tasks,reinforcing the reliability of WSNs with cluster-based communication protocols.